Plantation crops for socio-economic upliftment - Kumar, NK Krishna; Janakiram, T; Anandraj, M; Thomas, Lijo (Indian Horticulture, 2019)
The plantation crop sector can evolve as a major determinant of growth of agriculture sector while retaining its relevance for the industrial sector as a provider of raw materials. The road to achieve this scenario is full of challenges and it requires unstinting resolve and determination to pursue the path. A well-reasoned and cohesive application of cutting edge research, institutional support for development and creative policy initiatives for creating an enabling atmosphere can create a vibrant plantation crop economy in the country.